PERANCANGAN DINDING PENAHAN TANAH PADA BASEMENT DENGAN DUKUNGAN STRUT-BEAM - Renaldo Livando; Aksan Kawanda (JMTS: Jurnal Mitra Teknik Sipil, 2020)
Basement development in the construction world has become common. The contractor is expected to be able to master the knowledge for the construction of the basement. In practice, it cannot use only one or two methods to be used in each field condition. Many things must be estimated to design a structure, in addition to choosing the shape of the retaining wall used, the selection of support becomes something that must really be considered by looking at field conditions. An example that must be considered in designing a retaining wall itself is the stress of the soil that must be calculated appropriately so as not to damage the retaining wall itself. In addition, the relationship used between projects with deep or shallow excavations. If the retaining wall is lacking or not strong enough to withstand the stresses of the soil, it must be assisted with a support system that will withstand some of the lateral pressure exerted by the soil. In this analysis, the focus of the discussion is on the support system strutting model or can be called a strut-beam that is used to support the diaphgarm wall.